Effect of Papaverine on Human Serum Albumin Glycation - A Ahmadzadeh; M Feizie; R Ghafarzadegan (Institue of Medicinal Plants, ACECR, 2012)
Background: Glycation is a non enzymatic reaction initiated by the primary addition of sugar to the amino groups of proteins.In the early stage of glyction, the synthesis of intermediates leading to formation of Amadori compounds occurs. In the late stage, advanced glycation end product (AGE) are irrevesibly formed after a Complex cascade of reaction. Objective: Survey effect of Papaverine on Human Serum Albumin Glycation. Methods: In this study HSA incubate with Glucose and different papaverine concentration for 42 days at 37˚C. also HSA incubate alone (control sample), with Glucose(glycated sample) and with different papaverine concentration (without Glucose) respectively under the same conditions. Then samples survey with circular dichroism, fluorescence and UV spectroscopy. Results: HSA glycation increase in proportion to papaverine concentration. samples contain Glucose and papaverine show more change in secondary structure ,free amino groups and AGE fluorescence in relation to glycated and control samples. Conclusion: In glycated α helix and β sheet show 5.7% decrease and 3.1 % increase in comparison to control respectively. glycated show 14.2 % fluorescence more than control. Free lys number in glycated show 8% less than control sample. all this cases show more change in samples which contain papaverine and Glucose. seem papaverine change HSA and cause more lys contact with sugar thus papaverine increase glycation.